Hypoactive Sexual Desire Disorder - entity and therapeutic approaches: An overview - C. da Costa Campos; J. Mesquita (Psicosomática y Psiquiatría, 2021)
Introduction: Sexuality is a very important part of the human life and nature. Hypoactive sexual desire disorder (HSDD) is the most common form of female sexual dysfunction, especially among pre-menopausal women. The purpose of this review is to outline an overview of female sexual dysfunctions, particularly regarding HSDD, its pathophysiological mechanisms and the existing treatment approaches for this disorder, with special focus on the only drug approved by the US Food and Drug Administration (FDA) for the treatment of this disease.